Journey to Shariah Hospital:An Indonesian Experience - Ismail, Siti Aisyah; Hamid, Burhanuddin; Sulistiadi, Wahyu; Sagiran, - (International Journal of Human and Health Sciences (IJHHS), 2018)
Objective: As the world’s most populous Muslim country, Indonesia carries the responsibilityto establish an Islamic healthcare system that are of superior quality. Believing that Islamic Shariah is the best system for any activity, the need to translate the system into a measurable and objective healthcare quality tools are eminent. In 2015 the Standard of Shariah Hospital Certification were published and in 2016 the National Shariah Council produced a fatwa on the implementation of Shariah Hospital. In 2017, a second version of the Standard were published to be formalized by the National Shariah Council as the awarding body. In this article, the working principles of a hospital practicing the Shariah provisions in Indonesia will be explained. Approach and Value: The concept uses the maqasidic approach in it’s structure and refers to the National Hospital Accreditation Commission format. Normative standards are conserved and Shariah values are added in all critical points. Further technical details are produced to ensure proper implementation of the standards, which are divided into Shariah management and Shariah services. Two hospitals were appointed as the pilot project and many more are awaiting it’s implementation. As a conclusion it can be said that Shariah Hospital Certification standards provides added value on top of the national hospital accreditation standards. Hospital performance are expected to improve through the implementation of Shariah Hospital Certification by means of establishing quality work culture in hospital staffs through the inculcation of shariahvalues International Journal of Human and Health Sciences Vol. 02 No. 02 April’18. Page : 55-64